Crossing the Rift Resources, Settlements Patterns and Interaction in the Wadi Arabah - Bienkwoski, P.; Galor, Katharina (Council for British Research in the Levant, 2006)
Most of the papers published in this volume were originally presented at a conference of the same name, organised by the editors, and held in Atlanta, Georgia, in November 2003. The Wadi Arabah falls between the two areas of southern Jordan and Negev, and has traditionally been seen as a barrier and border. This book (and the conference it came out of) is an attempt to look at this neglected area anew: bridge, rather than barrier.